Hypoxia Inhibits Osteogenesis and Promotes Adipogenesis of Fibroblast-like Synoviocytes via Upregulation of Leptin in Patients with Rheumatoid Arthritis - Menglei Ding; Yu Cheng; Zhen Xu; Ying Lu; Jing Li; Liu Lu; Ming Zong; Lieying Fan (Journal of Immunology Research)
Hypoxia is associated with the pathogenesis of rheumatoid arthritis (RA). RA fibroblast-like synoviocytes (FLSs) are able to differentiate into osteoblasts and adipocytes. In this study, we aimed to investigate the role of hypoxia in the osteogenesis or adipogenesis of RA-FLSs. Bioinformatics analysis was performed to profile gene expression in the datasets of GSE21959, GSE32006, and GSE55875, and flow cytometry was performed for FLS characterization, while Alizarin Redand Oil Red O staining for osteogenic or adipogenic differentiation of FLSs, respectively. RNA interference leptin knockdown was used to determine the role of leptin in the osteogenesis and adipogenesis of RA-FLSs, and the expression of osteogenic and adipogenic markers was quantified by RT-qPCR and Western blotting. FLSs exhibited a mesenchymal stem cell (MSC)-like phenotype and we observed a limited self-renewal capacity in RA-FLSs compared to that in MSCs, but it was still greater than osteoarthritis (OA)-FLSs. Hypoxia did not change the RA-FLS MSC-like phenotype but inhibited the osteogenic differentiation and promoted the adipogenic differentiation of RA-FLSs. From the bioinformatics analysis ofGSE21959, GSE32006, and GSE55875 datasets, we found leptin, the only perturbed hypoxia-mediated upregulated gene across the three profiled datasets. Leptin knockdown in RA-FLSs reversed the hypoxia-mediated reduction of osteogenesis and hypoxia-mediated enhancement of adipogenesis by elevated expression of osteogenic markers and reduced expression of adipogenic markers, respectively. Therefore, hypoxia-leptin regulation of the osteogenic and adipogenic differentiation of RA-FLSs advances our understanding of RA pathogenesis, meanwhile also provides opportunities for future therapeutic intervention of RA.